1.2 MW peak power, all-solid-state picosecond laser with a microchip laser seed and a high gain single-passing bounce geometry amplifier. (November 2016) - Wang, Chunhua; Shen, Lifeng; Zhao, Zhiliang; Bin Liu; Jiang, Hongbo; Chen, Jun; Liu, Chong
Abstract: A semiconductor saturable absorber mirror (SESAM) based passively Q-switched microchip Nd:YVO4 seed laser with pulse duration of 90 ps at repetition rate of 100 kHz is amplified by single-passing a Nd:YVO4 bounce amplifier with varying seed input power from 20 µW to 10 mW. The liquid pure metal greasy thermally conductive material is used to replace the traditional thin indium foil as the thermal contact material for better heat load transfer of the Nd:YVO4 bounce amplifier. Temperature distribution at the pump surface is measured by an infrared imager to compare with the numerically simulated results. A highest single-passing output power of 11.3 W is obtained for 10 mW averaged seed power, achieving a pulse peak power of ~1.25 MW and pulse energy of ~113 µJ. The beam quality is well preserved with M 2 ≤1.25. The simple configuration of this bounce laser amplifier made the system flexible, robust and cost-effective, showing attractive potential for further applications. Highlights: Liquid metal greasy was used as the thermal contact for better heat load transfer. Single-passing output as high as 11.3 W was obtained from a 10 mW picosecond seed. The system is all solid-state with very high gain, making it flexible and robust.